Vatersehnsucht. Botho Strauß erzählt sich seine Herkunft - Denka, Andrzej (Studia Germanica Posnaniensia, 2017)
Botho Strauß (b. 1944), German playwright, novelist and essayist, devotes his book Herkunft [Origin] (2014) to a subtle portrait of his slightly underestimated father, who died in 1971. This sample of prose is typical of Strauss as it encompasses meditative descriptions, disquisitions, aphorisms and narrative fragments. This narration contains numerous biographical details about his father, as well as his mother and the writer himself, and it tells us a lot about his youth and cultural maturation. Strauss’ hometown, Bad Ems, provides a certain topographic point of reference here. This is a highly personal and emotional text which simultaneously exhibits all esthetic properties that characterize Strauss’ style. This text is also about the way different sensory stimuli incite our memory and how difficult it is to find a literary form adequate to reconstruct memory.